Geo-electrical resistivity survey for fresh groundwater investigation in Mirsharai Economic Zone, Chittagong in the south-eastern coastal areas of Bangladesh - Woobaidullah, A.S.M.; Islam, Md. Ariful; Hossain, Md. Zakir; Islam, Md. Shahidul (Journal of Nepal Geological Society, 2020)
Salinity in the groundwater is one of the major concerning issues in the coastal region of Bangladesh. Mirsharai Economic Zone, Mirsharai Upazila in the south-eastern coastal region of Chittagong District of Bangladesh, requires substantial amount of fresh groundwater supply for industrial and household use. The purpose of this study is to delineate the aquifer system of the study area and to determine the extension of potential fresh water aquifer for groundwater development through geophysical electrical resistivity sounding survey. Vertical Electrical Sounding in conjunction with borehole data provides information about the saline-fresh water interface, depth distribution, thickness of the fresh-water aquifers and local lithology. Lithological cross section shows that the sedimentary deposition and aquifer-aquitard distribution of this region are irregular even within a short spatial distance. The surface layer of top soil of clay or silty clay composition identified as aquitard shows resistivity in the ranges from 1.24 Ωm to 11 Ωm. This aquitard is underlain by a sand layer acting as shallow aquifer of varying thickness shows resistivity ranging mostly from 1.9 Ωm to 11Ωm reflecting the pore space water as saline to brackish. A second aquitard is underlain by the shallow aquifer of varying thickness. A deep fresh water aquifer, overlain by the second aquitard, shows resistivity in the range of 16 Ωm to73 Ωm indicating the pore space water as fresh. But the aquifer is interrupted by clay/silty clay layersat the deeper part in the middle portion. This study provides depth to the fresh water aquifer as wellas probable suitable regions for groundwater development.